2009
DOI: 10.1007/s10643-009-0309-0
|View full text |Cite
|
Sign up to set email alerts
|

Parents’ Perceptions of Child Care for Children with Disabilities

Abstract: Sixteen Minnesota families with children with disabilities participated in a 2-year interview study of their care experiences. Findings show that families developed a network of care providers, struggled to pay additional costs for care, were not informed of community services and programs, and believed that their children received adequate child care. This study highlights the need to provide information to families and providers and to link services in both rural and urban communities.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
7
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(7 citation statements)
references
References 16 publications
0
7
0
Order By: Relevance
“…Parents of children with disabilities struggle to access adequate and high‐quality day care, after‐school care and school services (Ceglowski et al, 2009; Hill & Moore, 2015). Adopted children are also more likely to receive special education services (Altarac & Saroha, 2007), possibly increasing challenges to securing adequate school services.…”
Section: Work Family and Community Resources In The Context Of Except...mentioning
confidence: 99%
“…Parents of children with disabilities struggle to access adequate and high‐quality day care, after‐school care and school services (Ceglowski et al, 2009; Hill & Moore, 2015). Adopted children are also more likely to receive special education services (Altarac & Saroha, 2007), possibly increasing challenges to securing adequate school services.…”
Section: Work Family and Community Resources In The Context Of Except...mentioning
confidence: 99%
“…Not surprisingly, education was the second most cited concern of parents in a study by Heiman (2002). Parents also reported challenges in accessing child care and after-school services (Ceglowski, Logue, Ulrich, & Gilbert, 2009; Jinnah & Stoneman, 2007). These barriers were either related to the absence of appropriate services or issues regarding access to available services.…”
Section: Factors Influencing Parental Healthmentioning
confidence: 99%
“…The importance of community resources as a direct influence and as a mitigating force on work–life fit indicates that more work still needs to be done to assure access to high-quality, affordable, and effective services. Problems in the adequacy and delivery of a wide range of relevant services, such as health care, child care, and schools, have been identified in several studies (Berry et al, 2010; Ceglowski et al, 2009; Rosenzweig et al, 2002), but there is still limited evidence on how this might specifically affect fathers of children with SHCN. Parette, Meadan, and Doubet (2010) stress in their report that service providers need to strive to engage fathers in services and acknowledge fathers’ unique experiences and expertise.…”
Section: Implications For Practicementioning
confidence: 99%
“…SHCNs are defined as any chronic physical, behavioral, developmental, or emotional issue that requires the use of services that exceeds service use of children without chronic conditions (McPherson et al, 1998, p. 138). Research demonstrated that families of children with SHCNs struggle to maintain employment (Brannan, Brennan, Sellmaier, & Rosenzweig, 2018; Porterfield, 2002; Sellmaier, Leo, Brennan, Kendall, & Houck, 2016) and to access much-needed support services (Ceglowski, Logue, Ullrich, & Gilbert, 2009; Stewart, 2013). They are also at greater risk of experiencing stress and strain than parents raising children without such needs (Darling, Senatore, & Strachan, 2012; Giallo et al, 2015).…”
mentioning
confidence: 99%
See 1 more Smart Citation